Membangun Budaya Berpikir Filsafat dalam Menumbuhkan Keyakinan Beragama - Zaini Fasya (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
Recently human attitudes and behaviors do not go through a mature and comprehensive thought process often occur. They are easily provoked so that many victims of mental and emotional oppression was deviations from the norms of communication, behave as if separated from ethics of politeness, cross borders values ​​and manners. Among them have an impact on religious and cultural attitudes that are used as tyranny, where in the name of God and ethnicity, people commit violence, oppression, injustice and murder. The research used the library research method that aimed to describe and obtain comprehensive knowledge related to the cultural meaning of philosophical thinking and to explain strategies in building a philosophical culture that can foster religious beliefs. The results of this study increased faith coupled with philosophical thinking in addition to knowing further behind a belief, our beliefs will also be stronger and not easily wear off.